Capacidade funcional e atenção em idosos praticantes de jogos de câmbio - Bess, Roseli (2015)
Considering the growth of the elderly population actions are necessary to maintain their functional capacity aiming to meet efficiently physical demands of everyday life. Among such actions the volleyball exchange game practice is an alternative that allows the elderly to take part in physical fitness. In this way, this study aimed to investigate the effects of volleyball exchange on functional capacity and attention on senior practitioners and will be described in detail in a scientific approach. 21 seniors between 62-84 years took part in this research in the northwest region of Rio Grande do Sul state Brazil. Most were female living in the urban area with medium-low levels of education. Attendees already practiced other physical activities such as walking and gymnastics. More than half had some health problems and was using drugs. The study had a control intervention before and after. The games were held twice a week lasting 60 minutes in 12 weeks. As research tools the Senior Fitness Test Protocol which measures the strength parameters, flexibility, aerobic endurance, speed, agility and balance, and the Test of Color Trails - Form 1 and Form 2 - assessing the sustained and divided attention were used. In the data analysis the Student t test for paired samples was applied. The associations between numerical variables were assessed using Pearson's correlation coefficient with significance value <0.05. The results indicated significant differences in overall physical fitness index (p <0.001). There were also significant differences in the tests that evaluate strength: get up and down (p = 0.004), forearm flexion (p <0.001); physical mobility: sitting, walking 2.44 m and sitting down again (p = 0.003); and aerobic endurance: walking 6 minutes (p <0.001). In colorful trails test analysis results showed an improvement in attention indicating significant differences in the two tests (Form 1 p <0.001 and Form 2 p <0.001). Both functional capacity and attention improved markedly with volleyball exchange practice. The data show the importance of preventive and therapeutic interventions through physical exercise to assist elderly in life quality in order to decrease the functional dependency and promote active aging. These findings suggest that the senior volleyball exchange game is an exercise alternative for maintaining functional capacity and health care to elderly people